Comparison of the Treatment Guidelines for Actinic Keratosis: A Critical Appraisal and Review. Issue 5 (September 2017) - Fleming, Patrick; Zhou, Stephanie; Bobotsis, Robert; Lynde, Charles
There are currently several reputable guidelines on the treatment of actinic keratosis (AK) from groups in Canada, the United Kingdom, and Europe. These recommendations, based on evidence or expert consensus, offer clinicians a variety of treatment options for the different clinical presentations of AKs. Although the guidelines are similar in some regards, variations exist in treatment options, duration, and strength of recommendation. Some guidelines also lack input on specific therapies and certain types of AK, such as hypertrophic or thin presentations. The purpose of this article is to review and compare guidelines published by Canadian, UK, and European groups for the management of AKs in patients.